Fostering Collaboration in Kindergarten through an Augmented Reality Game - Campos, Pedro; Pessanha, Sofia; Jorge, Joaquim (International Journal of Virtual Reality, 2011)
Kindergarten children are a very special class of users, since they are in a primary stage of life, when they must learn how to live in society, e.g. to listen and respect the others’ opinions, share the same objects and also help each other. This study presents an Augmented Reality game, in which kinder- garten children were able to collaborate in a spontaneous way supported by motivation, enjoyment and curiosity. This game allows children to explore concepts like the animals and the environments they live in by using Augmented Reality markers and a wooden board. These markers are the game pieces and through them children are able to manipulate 3D virtual models. Experiments were performed with several classes of students in different schools. Results suggest that the game is effective in maintaining high levels of motivation and collaboration among children, particularly when using immediate feedback